Estimating Skeletal Maturity Using Wrist Radiographs During Preadolescence: The Epiphyseal:Metaphyseal Ratio. Issue 7 (17th August 2022) - Huang, Lauren F.; Furdock, Ryan J.; Uli, Naveen; Liu, Raymond W.
Abstract : Background: Although skeletal maturity is most relevant during adolescence, it has utility in treatment of younger patients in some circumstances, such as scoliosis, limb length discrepancy, or endocrinopathies. Currently, a quick, accurate, and reproducible method of estimating skeletal maturity in preadolescents using wrist radiographs is lacking. Methods: Serial anteroposterior wrist radiographs taken at historical growth study visits leading up to the chronological age (CA) associated with 90% of the final height (an enhanced skeletal maturity standard as compared with peak height velocity) were analyzed in 102 children. Epiphyseal and metaphyseal widths of 5 physes were evaluated: distal radius, distal ulna, first metacarpal, third metacarpal, and fifth metacarpal. Ulnar styloid height and radial styloid height were also measured, for a total of 7 epiphyseal:metaphyseal radiographic parameters. Greulich and Pyle (GP) bone age was also measured. A combination of stepwise linear regression and generalized estimating equation analyses was used to produce a skeletal maturity estimation model incorporating demographics (CA and sex) and the epiphyseal:metaphyseal ratios significantly correlated with skeletal maturity. Results: A total of 273 left anteroposterior hand-wrist radiographs from 56 girls (163 radiographs, range 4 to 13 y) and 46 boys (112 radiographs, range 3.8 to 15 y) were included. The demographics+ratios model had better prediction accuracy than GP only and GP with demographics (0.44, 0.87, and 0.47 y mean discrepancy from actual skeletal age, P <0.05 for both comparisons). There was no significant difference in the rate of outlier skeletal age estimates, defined as an estimate >1 year off from the true skeletal age, between the demographics+ratios model and the demographics+GP model (5.9% vs. 8.4%, P =0.12). Conclusions: When combined with CA and sex data, measurement of the epiphyseal:metaphyseal ratios of the left first and third metacarpals allows for improved skeletal maturity estimation compared with the GP technique. Clinical Relevance: Our modified wrist skeletal maturity system offers a relatively quick and reproducible method for estimating skeletal maturity extending into the juvenile age range. This study is a level III retrospective study of longitudinal human growth data obtained from the Bolton Brush Collection in Cleveland, Ohio.